An Investigation on Factors Affecting the Teaching of Practical Assessment Tasks in the Senior Phase Technology Classrooms - Blose, Princess; Ndlovu, Elliot Charles (Research in Social Sciences and Technology- OpenED Network, 2023)
This paper investigated factors affecting the teaching of practical assessment tasks in the Senior Phase Technology classroom at Ehlanzeni District in Mpumalanga Province, South Africa. The study follows the case study design. Three teachers were purposively sampled from three different schools based on their experience in teaching Technology in the Senior Phase. This paper is grounded on the Cognitive Apprenticeship theory. Qualitative data were collected using interviews. The data was analysed thematically. The emerging themes from the study were teachers’ knowledge and skills, resources and class size as contributing factors affecting the execution of practical assessment tasks in the Senior Phase Technology classroom. The study findings have adverse effects on learners’ achievements in practical assessment tasks, especially in design process skills.